1995
DOI: 10.1111/j.1365-2826.1995.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide‐E‐1 Antagonizes the Action of Melanin‐Concentrating Hormone on Stress‐Induced Release of Adrenocorticotropin in the Rat

Abstract: The physiological role of melanin-concentrating hormone (MCH) in mammals is still very elusive, but this peptide might participate in the central control of the hypothalamopituitary adrenal (HPA) axis during adaptation to stress. Cloning and sequencing of the rat MCH (rMCH) cDNA revealed the existence of additional peptides encoded into the MCH precursor. Among these peptides, neuropeptide (N) glutamic acid (E) isoleucine (I) amide (NEI) is co-processed and secreted with MCH in rat hypothalamus. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 39 publications
3
38
0
2
Order By: Relevance
“…Plasma corticosterone levels were significantly greater in 6-7-month-old male Mch1r Ϫ/Ϫ mice relative to wild-type littermates (Table 1). This result is consistent with the finding that MCH administration reduces basal and stress-induced plasma adrenocorticotropic hormone levels in rats (24) and suggests that MCH1R may be involved in the regulation of adrenal function. Ci͞g of tissue; n ϭ 5 per genotype).…”
Section: Generation and Validation Of Mch1rsupporting
confidence: 82%
“…Plasma corticosterone levels were significantly greater in 6-7-month-old male Mch1r Ϫ/Ϫ mice relative to wild-type littermates (Table 1). This result is consistent with the finding that MCH administration reduces basal and stress-induced plasma adrenocorticotropic hormone levels in rats (24) and suggests that MCH1R may be involved in the regulation of adrenal function. Ci͞g of tissue; n ϭ 5 per genotype).…”
Section: Generation and Validation Of Mch1rsupporting
confidence: 82%
“…Trunk blood was collected in heparinised tubes, centrifuged immediately and the plasma separated and kept frozen at −20°C until assayed. Due to the presence of circadian changes in hypothalamic mRNA content of the neuropeptides evaluated in this study [26][27][28][29][30], the animals (NL, SL and LL) from each experiment (two independent experiments) were killed on the same day (18.00-20.00 hours), just before the dark phase (20.00 hours). In order to completely avoid any possible circadian effect, the animals were killed in an alternate manner, i.e., one rat from each group (NL, SL, LL), rather than all the animals from one experimental group before starting the next group.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the processes described above, changes in many other metabolic processes also take places, which are vital for normal functionality of an organism. It has been found that stress results in quantitative changes in some hormones, such as glucocorticoid, catecholamin and melatonin [35,36]. Therefore, the objective of our current research is to establish the quantitative changes of the hormones under psycho-emotional stress, such as isolation and violation of circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%